Assessing Habitat Availability in a Hydrodynamic Reservoir System. (20th November 2022) - Schriener, William; Koupal, Keith; Wuellner, Melissa; Ranglack, Dustin H.
Abstract: Habitats may become unavailable to fish in reservoirs at different water elevations. Coves are particularly vulnerable to habitat loss, as these peripheral zones may become isolated from the main reservoir. Quantifying habitat loss at different water elevation reductions and estimating the cost of replacing specific types of habitat or maintaining a target percentage of total habitat cover can help fisheries managers to plan for habitat restoration projects in reservoirs. We used side‐scan sonar to estimate areas of rock, tree, and brush habitat in one cove within Harlan County Reservoir, Nebraska, and used quotes for materials, placement, and personnel from recent habitat restoration projects to estimate replacement and maintenance costs. Materials included riprap rock, cedar trees, and those needed to construct Georgia cubes. Overall, rock, brush, and trees covered a total of 2% of the cove at conservation pool. Rock habitat covered 10 times more area than brush and 100 times more area than trees. All habitats became unavailable when water elevation decreased by 3.5–4.0 m. The cost to replace each habitat type increased as water elevation decreased, and the total cost to replace all habitat at 3.5 m of elevation loss was US390, 000. The cost to maintain the original area of habitat available in the cove (2% of the total cove area) increased for each type of habitat but only until water elevation decreased by 2.5 m. At this point, the total cost to maintain similar habitat coverage was 219, 000. Climatic variability may lead to greater oscillations of water elevations in reservoirs, making the vertical distribution of available habitat even more relevant to management planning. The findings of this study serve as an example for how managers can identify the vertical distribution of available habitats and estimate costs for habitat restorations.